1998
DOI: 10.1007/s001340050712
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter-related bloodstream infections: an analysis of incidence and risk factors in a cohort of 400 patients

Abstract: We have defined the incidence of CR-BSI in a cohort of patients from a tertiary referral hospital, the rates comparing favourably with those reported for similar populations. We were unable to demonstrate significant differences in any patient or catheter variables between those with and without CR-BSI. The AOLC test used alone was unhelpful as a method to diagnose in situ CVC infection in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 25 publications
1
28
0
3
Order By: Relevance
“…More recently, Tighe 27 have demonstrated that a policy of selective removal of catheters based on the AOLC test was safe, feasible, and cost effective. In contrast, Gowardman et al 28 in a cohort of 400 patients, demonstrated that in the 12 patients with CRBI the AOLC test was negative in all cases. They concluded that the AOLC test used alone was unhelpful as a method of diagnosing in situ CVC infection, consistent with the findings of Tighe et al, 26 but in sharp contrast to those reported by Rushforth et al 25 Recently, Farina et al 29 showed in a pediatric population that the AOLC test did not aid diagnosis of CRBI.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…More recently, Tighe 27 have demonstrated that a policy of selective removal of catheters based on the AOLC test was safe, feasible, and cost effective. In contrast, Gowardman et al 28 in a cohort of 400 patients, demonstrated that in the 12 patients with CRBI the AOLC test was negative in all cases. They concluded that the AOLC test used alone was unhelpful as a method of diagnosing in situ CVC infection, consistent with the findings of Tighe et al, 26 but in sharp contrast to those reported by Rushforth et al 25 Recently, Farina et al 29 showed in a pediatric population that the AOLC test did not aid diagnosis of CRBI.…”
Section: Discussionmentioning
confidence: 85%
“…Seven studies 16,[25][26][27][28][29][30] have been performed to assess the validity of the Gram stain-AOLC test for the diagnosis of CRBI in non-neutropenic patients. Rushforth et al, 25 in an infant population, found the test 87% sensitive and 94% specific in the diagnosis of central catheter-related sepsis, as defined by quantitative blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…These included blood samples from a healthy individual with and without spiking with bacteria. An extraction control of blood spiked with 10 3 CFUs of Staphylococcus epidermidis/µl was found to yield DNA levels close to the lower limit of detection. Bacterial DNA controls containing known amounts of bacterial DNA extracted from Enterococcus faecalis (100 pg to 100 fg) and a negative control (with no DNA in the reaction) to detect reagent contamination), were also included in each run.…”
Section: Molecular Methodsmentioning
confidence: 85%
“…10,11 Discrimination between the CVC and other sources of bloodstream infection is important because treatment strategies differ. In addition to systemic antibiotics, CVC-associated infection requires either antibiotic treatment that is targeted at microbial colonisation of the CVC lumen by being left in the CVC lumen, or instilled slowly, or removal of the CVC.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation